Listrik dan Perubahan Sosial Pada Masyarakat Desa Terpencil Studi Kasus pada Masyarakat Dusun Punik, Kecamatan Batu Lanteh, Kabupaten Sumbawa - Taufiq Ramdani (Jurnal Kawistara, 2020)
Electricity has been a vital force of soclial change. Access to electricity is an inevitable drive to multidmentional transfromation of society. The purpose of this research is to describe the forms of social change that occurs in Punik remote rural communities as a result of the presence of diesel generating electrical power (generator) in 2005. Based on a qualitative conducte in Punik Village of Batu Lanteh Subdistrict of Sumbawa regency, this research found the following conclusions: (a) shifts in the layers of social status, which is based on the extent of the diversity of manifestations and clumps of technology that can have, how expensive, how far the complexity or level of sophistication, how people are able to do and have it , (b) changes in the distribution of roles in the family and society, where the role of the family and society to adapt following the relative availability of resources beyond the normative criteria, namely gender and age, (c) shifts in basis and the orientation of interaction and cooperation of the elements of intimacy that strengthen kinship and altruism shifted into affective neutrality, individual and economy-oriented interests, (d) shift in the tradition, includig a variety of oral tradition that includes the inauguration of the relationship between individuals that is reduced by functions clump technology innovation; other collective traditions are relatively easier stimulus delivered through the entertainment medi; (e) The change of culture, a culture which previously relied on a livelihood, the human role and traditional equipment based technologies manifestation are displaced by electrical function, (f) the changes social events to adapt with electrical availability.Keywords: Diffusion; Electricity; Generator; Innovations; Remote Indigenous Communities; Social Change.